The Investigation of the protective effects of hydro-alcoholic extract of sea buckthorn (Hippophaerhamnoides L.) in spermatogenesis of rat after exposure of Wi-Fi radiation - Hosseinyzadeh, Zohreh; Shojaeefard, Manzarbanoo; Hooshiyar, Mansooreh; Firozi Dalvand, Leila; Pooladi, Mehdi (Archives of Advances in Biosciences, 2015)
Male infertility is a distressingly common condition affecting about 1 in 20 of the male population. In a majority of the cases, the male partner produces sufficient numbers of spermatozoa to achieve fertilization but there are functional defects in these cells that prevent conception from occurring. In this study, the effects of Wi-Fi radiation on spermatogenesis, testes and testosterone of large white male rats were studied, and also hydro alcoholic extract of sea buckthorn fruit were used as a protective agent against the effects of Wi-Fi radiation, and the comparative study was done.For this study 60 white male laboratory rats weighing 200-250 g were selected then tested in good conditions of light and food. The mice were randomly divided in terms of Wi-Fi Radiation and received gavage Sea buckthorn into 6 out of groups of 10.It was found that in the groups that had received Wi-Fi radiation, waves did not affect sperm count, testes weight, testosterone and testicular tissue, but it caused a significant decrease in fertilized sperm motility, and sea buckthorn extract could work as a protective agent against the radiations. According to the results of this research, it can be the probability that Sea buckthorn extract, having antioxidant substance can prevent destructive effects of waves that cause free radicals and having vitamin E improves sperm quality.